2007
DOI: 10.1177/0010880406294473
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Customer-Derived Value in the Timeshare Industry

Abstract: The timeshare sector has grown substantially over the past decade in both size and product configuration. Focusing on the concept of customer-derived value, group interviews were conducted with owners of timeshare holiday products to assess the dimensions of customer value in timeshares. Twelve such dimensions of value emerged from the interviews, most notably knowledge enhancement. Six detractors of derived value were identified. With a better understanding of the sources of value for timeshare owners, manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 17 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Moreover, Shieh and Cheng (2007) tested a consumer behavioral model of adolescent and young adult online gamers and proposed that experiential constructs (social function, empathy and escapism) positively impact satisfaction. Furthermore, Sparks et al (2007) found that consumer values positively and significantly correlate with satisfaction with timeshare product. Based on these findings, this investigation hypothesizes that satisfaction increases with experiential value.…”
Section: Experiential Valuesmentioning
confidence: 96%
“…Moreover, Shieh and Cheng (2007) tested a consumer behavioral model of adolescent and young adult online gamers and proposed that experiential constructs (social function, empathy and escapism) positively impact satisfaction. Furthermore, Sparks et al (2007) found that consumer values positively and significantly correlate with satisfaction with timeshare product. Based on these findings, this investigation hypothesizes that satisfaction increases with experiential value.…”
Section: Experiential Valuesmentioning
confidence: 96%
“…Ocean beach areas ranked second with 50.3%, followed by mountain, lakes, historical sites, cultural venues, and golf resorts, each representing 36.2, 24.2, 23.8 and 22% preference, respectively. Timeshare owners also cited satisfaction with their interval ownership because they have the opportunity to holiday, relax and spend quality time with family, meet and socialize with other timeshare members, and share memorable learning experiences (RCI, 2003;Sparks et al, 2007).…”
Section: Timesharementioning
confidence: 99%
“…This research found that timeshare owners were motivated to purchase timeshare based on exchange opportunities (flexibility of location), financial savings, resort features (amenities) and quality of accommodation. Further insights into this issue come from a recent study by Sparks et al (2007). Using qualitative group interviews, they identified twelve dimensions of value that might be relevant to timeshare accommodation.…”
Section: Timeshare Accommodationmentioning
confidence: 99%
“…A questionnaire was developed from three sources: (1) comments from timeshare owners who participated in focus groups conducted (see Sparks et al, 2007); (2) an industry expert panel; and (3) extant literature (e.g., Woodall, 2003). For the focus groups, current timeshare owners were brought together and interviewed in three separate sessions.…”
Section: The Questionnairementioning
confidence: 99%